The value of multimodal ultrasound imaging in differentiating HER2-positive breast cancer - Lei, Yu-Meng; Liu, Chen; Lei, Bing-Song; Liao, Chen; Zhang, Ning; Wang, Qi; Zeng, Shu-E; Zhang, Ge; Ye, Hua-Rong (Frontiers in Oncology, 2026)
ObjectivesThis study investigated vascular differences between human epidermal growth factor receptor 2 (HER2)-positive and HER2-negative breast cancers using multimodal ultrasound and evaluated their diagnostic utility.MethodsBreast masses were examined with conventional ultrasound (CUS), color Doppler flow imaging (CDFI), contrast-enhanced ultrasound (CEUS), and super-resolution ultrasound (SRUS). Quantitative and qualitative parameters were extracted. Binary logistic regression was used to identify independent predictors of HER2-positive breast cancer. The diagnostic performance was evaluated by receiver operating characteristic (ROC) curve.Results72 breast masses were divided into HER2-positive (n = 23) and HER2-negative (n = 49) groups according to immunohistochemical results. Univariate analysis showed that 12 parameters of four ultrasound modalities were significantly different between the groups (p < 0.05), whereas multivariate analysis showed differences in 8 parameters. Maximum diameter of the lump, microcalcification, peak intensity and max flow velocity of HER2-positive group were significantly greater than HER2-negative group (p < 0.05). HER2-positive group showed greater lesion extent after CEUS, less mean tortuosity, more uniform microvasculature distribution and microvasculature flow direction was away from the transducer (p < 0.05). The combination of CUS, CEUS, and SRUS achieved the highest area under the curve (AUC) of 0.976, with sensitivity, specificity and accuracy of 95.7%, 93.9% and 94.4%, respectively.ConclusionsMultimodal ultrasound parameters from CUS, CEUS, and SRUS can predict HER2-positive breast cancer, and their combination provides superior diagnostic efficacy.